FRI0427 EULAR RECOMMENDATIONS FOR INTRA-ARTICULAR TREATMENTS FOR ARTHROPATHIES. (2nd June 2020) - Uson Jaeger, J.; Naredo, E.; Rodriguez-García, S. C.; Castellanos-Moreira, R.; O'neill, T.; Pandit, H.; Doherty, M.; Boesen, M.; Möller, I.; Vardanyan, V.; De la Torre-Aboki, J.; Terslev, L.; et al.
Abstract : Background: Intra-articular therapies (IAT) are widely used in clinical practice to treat patients with rheumatic and musculoskeletal diseases (RMDs). Many factors influence their efficacy and safety. There is a wide variation in the way IATs are delivered by health professionals. In an attempt to standardise these procedures, evidence-based recommendations are the right way forward. Objectives: To establish evidence-based recommendations to guide health professionals using IAT in adult patients with peripheral arthropathies. Methods: At a first face-to-face meeting, the results of an overview of systematic reviews were presented to the multidisciplinary task force of members from 8 countries. The aim, scope and outline of the taskforce were also established at this meeting. Thirty-two clinical questions ranked for priority (relevance for practice plus feasibility) drove the systematic reviews performed by two fellows. In addition, two surveys addressed to physicians, health professionals and patients throughout Europe were agreed to acquire more background information. At the second face-to-face meeting, the evidence for each research question was discussed, and each recommendation shaped and voted in a first Delphi round. Level of agreement was numerically scored 0 to 10 (0 completely disagree, 10 completely agree). All panellists voted anonymously using a sli.do app. Agreement needed to be greater than 80% to be included in a second Delphi round, which also allowed reformulation of statements. Finally, a third Delphi round was sent to the taskforce. The level of evidence was assigned to each recommendation according to the EULAR SOP for establishing recommendations. Results: Recommendations focus on practical aspects for daily practice to guide health professionals before, during and after IAT in adult patients with peripheral arthropathies. Five overarching principles were established, together with 11 recommendations that address the following issues: (1) patient information; (2) procedure and setting; (3) accuracy issues; (3) routine and special antiseptic care; (4) safety issues and precautions to be addressed in special populations; (5) efficacy and safety of repeated joint injections; (6) the usage of local anaesthetics; and (7) aftercare. The document includes the supporting evidence and results from the surveys, level of evidence and agreement. Conclusion: We have developed the first evidence and expert opinion based recommendations to guide health professionals using IAT. Acknowledgments: Eular Taskforce grant CL109 Disclosure of Interests: Jacqueline Uson Jaeger: None declared, Esperanza Naredo: None declared, Sebastian C Rodriguez-García Speakers bureau: Novartis Farmaceutica, S.A., Merck Sharp & Dohme España, S.A., Sanofi Aventis, UCB Pharma, Raul Castellanos-Moreira: None declared, Terence O'Neill: None declared, Hemant Pandit Grant/research support from: Glaxo Smith Kline (GSK) for work on Diclofenac Gel, Speakers bureau: Bristol Myers Squibb for teaching their employees about hip and knee replacement, Michael Doherty Grant/research support from: AstraZeneca funded the Nottingham Sons of Gout study, Consultant of: Advisory borads on gout for Grunenthal and Mallinckrodt, Mikael Boesen Consultant of: AbbVie, AstraZeneca, Eli Lilly, Esaote, Glenmark, Novartis, Pfizer, UCB, Paid instructor for: IAG, Image Analysis Group, AbbVie, Eli Lilly, AstraZeneca, esaote, Glenmark, Novartis, Pfizer, UCB (scientific advisor)., Speakers bureau: Eli Lilly, Esaote, Novartis, Pfizer, UCB, Ingrid Möller: None declared, Valentina Vardanyan: None declared, Jenny de la Torre-Aboki: None declared, Lene Terslev: None declared, Francis Berenbaum Grant/research support from: TRB Chemedica (through institution), MSD (through institution), Pfizer (through institution), Consultant of: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Bone Therapeutics, Regulaxis, Peptinov, 4P Pharma, Paid instructor for: Sandoz, Speakers bureau: Novartis, MSD, Pfizer, Lilly, UCB, Abbvie, Roche, Servier, Sanofi-Aventis, Flexion Therapeutics, Expanscience, GSK, Biogen, Nordic, Sandoz, Regeneron, Gilead, Sandoz, Maria Antonietta D'Agostino Consultant of: AbbVie, BMS, Novartis, and Roche, Speakers bureau: AbbVie, BMS, Novartis, and Roche, Willm Uwe Kampen: None declared, Elena Nikiphorou: None declared, IRENE Pitsillidou: None declared, Loreto Carmona Grant/research support from: Novartis Farmaceutica, SA, Pfizer, S.L.U., Merck Sharp & Dohme España, S.A., Roche Farma, S.A, Sanofi Aventis, AbbVie Spain, S.L.U., and Laboratorios Gebro Pharma, SA (All trhough institution)